2002
DOI: 10.1007/s00792-001-0261-4
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the enantioselectivity of two homologous thermophilic carboxylesterases from Alicyclobacillus acidocaldarius and Archaeoglobus fulgidus by random mutagenesis and screening

Abstract: The esterase genes est2 from Alicyclobacillus acidocaldarius and AF1716 from Archaeoglobus fulgidus were subjected to error-prone PCR in an effort to increase the low enantioselectivity of the corresponding enzymes EST2 and AFEST, respectively. The model substrate ( RS)- p-nitrophenyl-2-chloropropionate was chosen to produce ( S)-2-chloropropionic acid, an important intermediate in the synthesis of some optically pure compounds, such as the herbicide mecoprop. In the case of EST2, a single mutant, Leu212Pro, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Biochemical investigation demonstrated that EST2 optimally hydrolyzes esters with acyl chain length of six or eight carbon atoms because of the small dimension of its acyl-binding pocket (6,8). Kinetic and structural studies allowed us to propose the mechanism depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biochemical investigation demonstrated that EST2 optimally hydrolyzes esters with acyl chain length of six or eight carbon atoms because of the small dimension of its acyl-binding pocket (6,8). Kinetic and structural studies allowed us to propose the mechanism depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Instantaneous 'bursts' of pNP measured after addition of wild type or M211S/R215L enzymes to the assay mixtures. Shown are the readings at 405 nm and at zero time of assay mixtures containing pNP-hexanoate (C 6 ) or pNP-dodecanoate (C 12 ) after the addition of the indicated amounts of wild type (empty circles for C 6 and empty squares for C 12 ) or M211S/R215L (filled circles for C 6 and filled squares for C 12 ). Data were corrected for the pNP release due to the onset of the catalytic activity during the 4 s required to mix the enzyme with substrate and to read the absorption. )…”
Section: Measurement Of All Individual Kinetic Constants For the Est2mentioning
confidence: 99%
See 1 more Smart Citation
“…However, since the sequence identity was relatively low (<12 %) with other active hydrolases, this provides a novel dl-menthyl benzoate esterase as a starting biocatalyst for directed evolution and rational design, which may provide solutions to remarkably enhance the catalytic activity, enantioselectivity, and/or thermostability [35][36][37][38][39]. All these inspiring results aroused our interest to engineer the enantioselectivity, activity, and operational stability of AbMBH for potential application in menthol industry.…”
Section: Discussionmentioning
confidence: 95%
“…inra.fr/ESTHER/) is the carboxylesterase-2 (EST2) isolated and cloned from the thermophilic eubacterium Alicyclobacillus acidocaldarius [for a review see Mandrich et al 2009]. In a previous study on EST2, it was shown that using organic solvents at low concentrations (4-5 %; v/v), such as acetonitrile (CH 3 CN), dimethylformamide (DMF), dimethylsulphoxide (DMSO), methanol (MeOH), ethylene glycol and diethyl ether, the catalytic activity increases (Mandrich et al 2012) and the presence of solvents affects the enantioselectivity, expressed in a model hydrolytic reaction, using (RS)-p-nitrophenyl-2-chloropropionate, as substrate (Manco et al 2002). The analysis of the kinetic properties has shown that the action of EST2 is restricted to solutions of short acyl chain esters (Manco et al 1998).…”
Section: Introductionmentioning
confidence: 99%